A Survey on the Impact of Accounting Information System on Tasks Efficiency: Evidence from Malaysian Public Sector Agencies - Zakaria, Wan Zuriati Wan; Ilias, Norazlina; Wahab, Norlidawahi (International Review of Management and Marketing, 2017)
The purpose of the study is to assess the impact of accounting information system on the users' tasks efficiency. The tasks efficiency is an important construct for measuring system success or effectiveness. It is because an effective system would assist and support users in performing their tasks efficiently. In the study, accounting information system is referred to the computerised accounting information system, which was developed for facilitating organisations to gather, store and disseminate data for the purpose of planning, controlling, coordination, analysis and decision-making. The study was conducted using a set of questionnaire distributed to the users of accounting information system in selected Malaysian public sector agencies. The findings led to the conclusion that the current accounting information system used has significant impact on their tasks efficiency on the typical processes related to budgeting, financial reporting, auditing and financial controlling in the agencies. Keywords: Tasks Efficiency, Accounting Information System, Public Sector Agencies JEL Classification: M3